2007
DOI: 10.1186/1471-213x-7-88
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression patterns of let-7 microRNA in the silkworm (Bombyx mori)

Abstract: Backgroundlin-4 and let-7, the two founding members of heterochronic microRNA genes, are firstly confirmed in Caenorhabditis elegans to control the proper timing of developmental programs in a heterochronic pathway. let-7 has been thought to trigger the onset of adulthood across animal phyla. Ecdysone and Broad-Complex are required for the temporal expression of let-7 in Drosophila melanogaster. For a better understanding of the conservation and functions of let-7, we seek to explore how it is expressed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 67 publications
3
38
0
1
Order By: Relevance
“…The loss of Dicer-1 in D. melanogaster results in embryogenesis defects (7) and disruption of olfactory neuron morphogenesis (8). Moreover, developmental expression patterns of selected miRNAs in D. melanogaster (11,12) and B. mori (13,17) have revealed that a number of them are up-regulated in the transition from larvae to pupae, and of these let-7 is the most thoroughly studied (18,19). In the transition to adult of D. melanogaster, let-7 is required for neuromusculature remodeling (4), for proper timing in wing cell cycle, and for the maturation of neuromuscular junctions (3).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of Dicer-1 in D. melanogaster results in embryogenesis defects (7) and disruption of olfactory neuron morphogenesis (8). Moreover, developmental expression patterns of selected miRNAs in D. melanogaster (11,12) and B. mori (13,17) have revealed that a number of them are up-regulated in the transition from larvae to pupae, and of these let-7 is the most thoroughly studied (18,19). In the transition to adult of D. melanogaster, let-7 is required for neuromusculature remodeling (4), for proper timing in wing cell cycle, and for the maturation of neuromuscular junctions (3).…”
Section: Discussionmentioning
confidence: 99%
“…Among the members, let-7a has identical sequence across various animal species from C. elegans to human. The increase in let-7 expression in late developmental stages has been reported in many organisms (Sempere et al 2002, Lancman et al 2005, Liu et al 2007, Wulczyn et al 2007. Previously, studies have shown the expression patterns of let-7 in vertebrates during development; however, the direct contribution of let-7 in development has not been demonstrated (Lancman et al 2005, Schulman et al 2005, Wulczyn et al 2007.…”
Section: Introductionmentioning
confidence: 95%
“…The bmolet-7 was stage-and tissue-specifically expressed in the silkworm. It was expressed in very low level from the first molt to the early third instar, expressed highly after the third molt, and the most abundant expression was observed after mounting, particularly after pupation (Liu et al 2007). Microarray analyses showed that bmo-let-7 expressed in all of the 10 tissues of fifth-instar day-3 larvae (head, body wall, ASG, PSG, midgut, fat body, ovary, testis, hemocyte and malpighian tubule) ).…”
Section: Discussionmentioning
confidence: 96%